What would a graph look like with the equation y=-2(x)2+3.the two next to the x means to the second power.
Please help me
2 answers
I forgot to put use the integers -3 to 3 to graph the equation.
For x = - 3
y = - 2 ( x ) ^ 2 + 3 = - 2 * ( - 3 ) ^ 2 + 3 = - 2 * 9 + 3 = - 18 + 3 = - 15
for x = - 2
y = - 2 ( x ) ^ 2 + 3 = - 2 * ( - 2 ) ^ 2 + 3 = - 2 * 4 + 3 = - 8 + 3 = - 5
for x = - 1
y = - 2 ( x ) ^ 2 + 3 = - 2 * ( - 1 ) ^ 2 + 3 = - 2 * 1 + 3 = - 2 + 3 = - 1
for x = 0
y = - 2 ( x ) ^ 2 + 3 = - 2 * 0 ^ 2 + 3 = - 2 * 0 + 3 = 0 + 3 = 3
for x = 1
y = - 2 ( x ) ^ 2 + 3 = - 2 * 1 ^ 2 + 3 = - 2 * 1 + 3 = - 2 + 3 = - 1
for x = 2
y = - 2 ( x ) ^ 2 + 3 = - 2 * 2 ^ 2 + 3 = - 2 * 4 + 3 = - 8 + 3 = - 5
For x = 3
y = - 2 ( x ) ^ 2 + 3 = - 2 * 3 ^ 2 + 3 = - 2 * 9 + 3 = - 18 + 3 = - 15
For graph
In google type :
functions graphs online
when you see list of results click on :
rechneronline.de/function-graphs
When page be open in blue rectangle type :
- 2 x ^ 2 + 3
set :
Range y-axis from - 15 to 5
and click option :
Draw
y = - 2 ( x ) ^ 2 + 3 = - 2 * ( - 3 ) ^ 2 + 3 = - 2 * 9 + 3 = - 18 + 3 = - 15
for x = - 2
y = - 2 ( x ) ^ 2 + 3 = - 2 * ( - 2 ) ^ 2 + 3 = - 2 * 4 + 3 = - 8 + 3 = - 5
for x = - 1
y = - 2 ( x ) ^ 2 + 3 = - 2 * ( - 1 ) ^ 2 + 3 = - 2 * 1 + 3 = - 2 + 3 = - 1
for x = 0
y = - 2 ( x ) ^ 2 + 3 = - 2 * 0 ^ 2 + 3 = - 2 * 0 + 3 = 0 + 3 = 3
for x = 1
y = - 2 ( x ) ^ 2 + 3 = - 2 * 1 ^ 2 + 3 = - 2 * 1 + 3 = - 2 + 3 = - 1
for x = 2
y = - 2 ( x ) ^ 2 + 3 = - 2 * 2 ^ 2 + 3 = - 2 * 4 + 3 = - 8 + 3 = - 5
For x = 3
y = - 2 ( x ) ^ 2 + 3 = - 2 * 3 ^ 2 + 3 = - 2 * 9 + 3 = - 18 + 3 = - 15
For graph
In google type :
functions graphs online
when you see list of results click on :
rechneronline.de/function-graphs
When page be open in blue rectangle type :
- 2 x ^ 2 + 3
set :
Range y-axis from - 15 to 5
and click option :
Draw